SUSTAINABLE URBAN DRAINAGE SYSTEMS AND INTEGRATED WATER RESOURCES MANAGEMENT: A PATHWAY TO ACHIEVING SUSTAINABLE WATER MANAGEMENT - Arne Finger; Jonas Lutz; Putu Aryastana (Journal of Infrastructure Planning and Engineering, 2024)
Integrated Water Resources Management (IWRM) is an essential approach for achieving the United Nations’ Sustainable Development Goals (SDGs), particularly Goal 6: “Clean Water and Sanitation.” This study explores the role of IWRM in supporting sustainable water management in Germany, a country renowned for its advanced environmental policies and innovative water management systems. By aligning with the European Union’s Water Framework Directive (WFD), Germany implements comprehensive strategies that integrate environmental protection, stakeholder collaboration, and transboundary water management. Key initiatives such as the Rhine River Restoration Project and the Danube Floodplain Restoration demonstrate Germany’s success in applying IWRM principles to improve water quality, restore ecosystems, and enhance flood resilience. Despite its progress, challenges remain, including agricultural runoff, industrial impacts, and climate change-induced risks. Recommendations for improving Germany’s IWRM include expanding data collection systems, strengthening pollution controls, promoting circular water economies, enhancing climate resilience, and increasing public engagement. Ultimately, Germany’s IWRM framework provides a model for sustainable water management globally, illustrating how collaborative governance, innovation, and adaptive strategies can support the achievement of SDG 6 and broader sustainable development objectives.